2013
DOI: 10.2116/analsci.29.113
|View full text |Cite
|
Sign up to set email alerts
|

Faraday Rotation Dispersion Measurements of Diamagnetic Organic Liquids and Simultaneous Determination of Natural Optical Rotatory Dispersion Using a Pulsed Magnetic Field

Abstract: We constructed an apparatus to measure the wavelength dispersion of the Faraday rotation in the visible region, and determined the Verdet constants of diamagnetic organic liquids, including aliphatic compounds, benzene derivatives, and naphthalene derivatives. These three groups were easily distinguished by the magnitudes of their Verdet constants. Based on the theory developed by Serber, we determined the enhancing effect of π*←π transitions on the visible-light Faraday rotation angles observed for aromatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…The Verdet constants of several liquids were also measured and summarized in Table . All observed values were in good agreement with those measured in the previous study . Therefore, it was concluded that quantitative FR images could be obtained using a rotation angle and Verdet constant measured by the present microscopic FR system.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The Verdet constants of several liquids were also measured and summarized in Table . All observed values were in good agreement with those measured in the previous study . Therefore, it was concluded that quantitative FR images could be obtained using a rotation angle and Verdet constant measured by the present microscopic FR system.…”
Section: Resultssupporting
confidence: 91%
“…Figure (a) is the plots of the average FR angle against the wavelength. The solid lines indicate the calculated value from the Verdet constants measured in the previous study, taking into account the present experimental condition ( l = 200 μm and B = 1.2 T). For every sample, the results were in good agreement with those measured with the nonmicroscopic apparatus for FR dispersion.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Unfortunately, diamagnetic organic molecules have relatively small Verdet constants in regions far from resonance. Typical Verdet constants are on the order of hundreds of degrees per tesla per meter in the visible wavelength region, displaying a continuous decline toward longer wavelengths. Only for the larger polythiophenes in specific conditions have larger Verdet constants been reported, on the order of 10 4 deg T –1 m –1 . However, these large Verdet constants currently lack a conclusive explanation.…”
Section: Introductionmentioning
confidence: 99%